Image-Guided Thermal Ablation as an Alternative to Surgery for Papillary Thyroid Microcarcinoma: Preliminary Results of an Italian Experience - Mauri, Giovanni; Orsi, Franco; Carriero, Serena; Della Vigna, Paolo; De Fiori, Elvio; Monzani, Dario; Pravettoni, Gabriella; Grosso, Enrica; Manzoni, Marco F.; Ansarin, Mohssen; Giugliano, Gioacchino (Frontiers in Endocrinology, 2021)
Purpose: to report the results of our preliminary experience in treating patients with papillary thyroid microcarcinoma (PTMC) with image-guided thermal ablation, in particular estimating the feasibility, safety and short-term efficacy Materials and methods: from 2018 patients with cytologically proven PTMC <10 mm were discussed in a multidisciplinary team and evaluated for feasibility of image-guided thermal ablation. In case of technical feasibility, the three possible alternatives (i.e., image-guided thermal ablation, surgery, and active surveillance) were discussed with patients. Patients who agreed to be treated with image guided thermal ablation underwent radiofrequency (RFA) or laser ablation under local anesthesia and conscious sedation. Treatment feasibility, technical success, technique efficacy, change in thyroid function tests, side effects, minor and major complications, patients satisfaction and pain/discomfort perception during and after treatment and disease recurrence during follow-up were recorded. Results: a total of 13 patients were evaluated, and 11/13 (84.6%) patients (9 female, 2 male, mean age 49.3 ± 8.7 years) resulted suitable for image-guided thermal ablation. All 11 patients agreed to be treated with image-guided thermal ablation. 3/11 (27.3%) were treated with laser ablation and 8/11 (72.7%) with RFA. All procedure were completed as preoperatively planned (technical success 100%). Technique efficacy was achieved in all 11/11 (100%) cases. Ablated volume significantly reduced from 0,87±0,67 ml at first follow-up to 0,17±0,36 at last follow-up (p = 0.003). No change in thyroid function tests occurred. No minor or major complications occurred. All patients graded 10 the satisfaction for the treatment, and mean pain after the procedure was reported as 1.4±1.7, and mean pain after the procedure as 1.2±1.1 At a median follow-up of 10.2 months (range 1.5 – 12 months) no local recurrence or distant metastases were found. Conclusions: image guided thermal ablations appear to be feasible and safe in the treatment of PTMC. These techniques hold the potential to offer patients a minimally invasive curative alternative to surgical resection or active surveillance. These techniques appear to be largely preferred by patients.